Andragogy Based E-Training Model for Early Childhood Education Educators (Universitas Negeri Semarang, 2023)
Learning virtual is built with a learning climate that is packaged in the form of interactive online design . The purpose of this research is to design, analyze, and develop an andragogy-based e-training model to improve the competency of Early Childhood Education educators. E-training is used to make it easier for educators to learn more flexibly, adjusting to the assumptions of adult learning. This research does not only discuss the management of e-training, but also explains adult learning in the digital era, with learning steps that are closely related to the learning needs of adults. The qualitative approach in this study involved 5 informants, including 2 educators, 1 manager, and 2 experts to provide feedback on the conceptual model developed, with data collection techniques through interviews, observation, discussion and documentation. The results of the study show that the learning climate for adults via the internet can be carried out, but it needs to start with conditions of learning readiness through learning contracts and the freedom of learning citizens to access material both synchronously and asynchronously which can be embedded on the training website